Analysis of Relative Importance on Electric Vehicle Conversion Intention - Kwon, Chul Hwan; Rim Byun, Ha (2021 21st ACIS International Winter Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing (SNPD-Winter), 2021)
The transportation sector is responsible for a large quantity of air pollutant emission. While electric vehicles are introduced as a method to dramatically reduce air pollutant emission, the sales of electric vehicles are relatively low compared to traditional vehicles running on fossil fuel. Past studies have analyzed the factors influencing the conversion intention of electric vehicles. However, they share the limitation of not being able to approach the subject in a comprehensive approach, bringing up the need for a new research.AHP analysis conducted on the data collected showed the relative effect of dimensions in the order of product quality, policy support, market environment, and consumption consciousness. For the factors, reliability and durability, purchase subsidies, performance, and charging infrastructure showed to have the most influence on the conversion intention of electric vehicles. The theoretical implications of this study is, with a comprehensive approach, the study was able to address the conversion intention of electric vehicles with multiple factors, identifying relatively unconsidered influencing factors. In addition, for the managerial implications, the study provides a guideline for policy making and the basis data for strategy establishment of automakers.